2007
DOI: 10.1007/s00418-006-0265-3
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of advanced glycation end-products (AGEs) and their receptor (RAGE) in polycystic and normal ovaries

Abstract: The aim of the present study was to investigate the localization/immunohistochemical distribution of AGEs and RAGE, as well as their putative signalling mediator NF-kappaB in ovaries of women with polycystic ovary syndrome (PCOS) compared to normal. Archival ovarian-tissue samples from biopsies of six women with PCOS and from six healthy of similar age women, were examined immunohistochemically with monoclonal anti-AGEs, anti-RAGE and anti-NF-kappaB(p50/p65) specific antibodies. In healthy women, AGE immunorea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
2
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(126 citation statements)
references
References 57 publications
3
106
2
15
Order By: Relevance
“…Previous observations have shown increased AGE deposition in granulosa cells from human polycystic ovarian tissue compared to controls [18], whereas in the present study, AGEs seem to localize in theca interna cells of H-AGE-fed normal female rats. It is likely that the source of AGEs, being either endogenous or exogenous, may play a role in localization of AGEs in the ovarian as well as in other tissues, as in the previous immunochemistry study of ovarian tissue, the source of these molecules could not be defined and the type of diet was not known in PCOS patients from which the ovarian tissue was obtained.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Previous observations have shown increased AGE deposition in granulosa cells from human polycystic ovarian tissue compared to controls [18], whereas in the present study, AGEs seem to localize in theca interna cells of H-AGE-fed normal female rats. It is likely that the source of AGEs, being either endogenous or exogenous, may play a role in localization of AGEs in the ovarian as well as in other tissues, as in the previous immunochemistry study of ovarian tissue, the source of these molecules could not be defined and the type of diet was not known in PCOS patients from which the ovarian tissue was obtained.…”
Section: Discussioncontrasting
confidence: 84%
“…In addition, increased immunostaining of AGE and RAGE was observed in the different compartments of the ovarian tissue in polycystic ovaries [18]. Furthermore, young women with PCOS demonstrated increased serum levels of AGEs after receiving a high-AGE diet [19].…”
Section: Introductionmentioning
confidence: 94%
“…AGEs, which are modified proteins, lipids, or nucleic acids that are nonenzymatically glycated and oxidized by glucose, damage cellular structures and have been implicated in a number of diseases [55]. Research has demonstrated a strong association between the AGE-RAGE (receptor for AGEs) system and certain aspects of PCOS, including obesity [56], insulin resistance [57] [58], granulosa cell dysfunction [59], and adipocyte dysfunction [60]. In their studies using a human granulosa cell line, Diamanti-Kandarakis et al [61] have shown that the AGE-RAGE system could be the cause of the ovulation failure commonly seen in PCOS.…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%
“…NFkB may contribute to the development of a pro-inflammatory and pro-oxidative state by stimulating the expression of numerous target genes, such as tissue factor, vascular cell adhesion molecule-1 (VCAM1), p21Ras, ERK1/2 (MAPK3/1) and RAGE itself (Tanaka et al 2000, Mukhopadhyay & Mukherjee 2005. Furthermore, AGE-RAGE signalling through the activation of NFkB has been reported to regulate the expression of inflammatory cytokines (such as tumour necrosis factor a (TNFa) and interleukin 1), PAI-1 and endothelin-1, contributing to the development of several inflammationrelated conditions and diseases such as atherosclerosis, diabetic nephropathy and retinopathy (Murphy et al 2005, Diamanti-Kandarakis et al 2007b.…”
Section: Introductionmentioning
confidence: 99%